The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/aoc.4071
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene‐substituted bis(ethynyl)anthracene compounds as anticancer agents

Abstract: Three compounds (1–3) were synthesized, where ethynylferrocene is substituted at different positions of anthracene and anthraquinone, and their biological properties were investigated. Compounds 1–3 were characterized using NMR and mass spectroscopies and confirmed by their single‐crystal X‐ray structure. They were also characterized from electronic and photophysical properties. All three crystal structures were optimized using density functional theory calculations. The presence of C–H⋅⋅⋅π interactions in 1–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…DNA serves as a primary target for various drugs . DNA binding is also one of the critical steps for the understanding of actual aroyl‐hydrazone based drugs design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA serves as a primary target for various drugs . DNA binding is also one of the critical steps for the understanding of actual aroyl‐hydrazone based drugs design.…”
Section: Resultsmentioning
confidence: 99%
“…[35] DNA Binding Study of L 1 -L 4 DNA serves as a primary target for various drugs. [40] DNA binding is also one of the critical steps for the understanding of actual aroyl-hydrazone based drugs design. It helps know the proper mechanisms which participate in the site-specific recognition of duplex DNA and synthesis of aroyl-hydrazone based pharmaceutical molecules.…”
Section: Tryptophan Quenching Experimentsmentioning
confidence: 99%
“…Based on the binding energy (−10.61 kcal/mol −1 ) and inhibition constant (16.74 nM), it was obvious that compound 2 had the best interaction with cancer-related Aurora A kinase protein of all the analogs in this series. Indeed, both molecular docking and cell cytotoxicity assays revealed that 2 was a more effective anticarcinogen when compared with 1 and 3 as it was capable of binding to DNA strands and triggering apoptosis [29]. Of particular interest was the antimicrobial agent Chloroquinocin 1, which was shown to be active against Gram-positive bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA) [12].…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Singh et al reported a di-Fc anthraquinone with alkyne linkages, which showed cytotoxicity against human melanoma cancer (A375) and cervical carcinoma (HeLa) cell lines. 40 That compound was also found to be relatively inactive against normal human embryonic kidney (HEK) cells, suggesting some selectivity. The mechanism of the observed anticancer activity was linked to interactions with proteins and DNA.…”
Section: Introductionmentioning
confidence: 99%